Targeting C3a/C5a receptors inhibits human mesangial cell proliferation and alleviates immunoglobulin A nephropathy in mice. (10th April 2017) - Zhang, Y; Yan, X; Zhao, T; Xu, Q; Peng, Q; Hu, R; Quan, S; Zhou, Y; Xing, G
Summary: Complement activation has a deep pathogenic influence in immunoglobulin (Ig)A nephropathy (IgAN). C3a and C5a, small cleavage fragments generated by complement activation, are key mediators of inflammation. The fragments exert broad proinflammatory effects by binding to specific receptors (C3aR and C5aR, respectively). However, no studies thus far have investigated the effects of C3a, C5a and their receptors on IgAN. We observed that C3aR and C5aR antagonists repressed IgA-induced cell proliferation and interleukin (IL)-6 and monocyte chemotactic protein 1 (MCP-1) production in cultured human mesangial cells (HMCs). Furthermore, an IgAN mouse model induced by Sendai virus infection was employed to investigate the effects of C3aR and C5aR on IgAN in vivo for the first time. Wild-type (WT) and several knock-out mouse strains (C3aR –/– or C5aR –/– ) were immunized intranasally with increasing doses of inactivated virus for 14 weeks and were subjected to two intravenous viral challenges during the time-period indicated. In the Sendai virus-induced IgAN model, C3aR/C5aR-deficient mice had significantly reduced proteinuria, lower renal IgA and C3 deposition, less histological damage and reduced mesangial proliferation compared with WT mice. Both C3aR deficiency and C5aR deficiency, especially C3aR deficiency, inhibited renal tumour necrosis factor (TNF)-α, transforming growth factor (TGF)-β, IL-1β, IL-6 and MCP-1 expression significantly. However, C3aR/C5aR-deficient and WT mice with IgAN did not differ with respect to their blood urea nitrogen (BUN) and serum creatinine levels. Our findings provide further support for the idea that C3aR and C5aR are crucially important in IgAN, and suggest that pharmaceutically targeting C3aR/C5aR may hold promise for the treatment of IgAN. Graphical Abstract: